Descriptive analysis of annual general meeting minutes on the corporate website in the context of Malaysian listed companies / Mohd Shazwan Mohd Ariffin, Siti Seri Delima Abdul Malak and Wan Nordin Wan-Hussin - Mohd Ariffin, Mohd Shazwan; Abdul Malak, Siti Seri Delima; Wan-Hussin, Wan Nordin (Universiti Teknologi MARA, 2021)
The annual general meeting (AGM) is a medium of communication between the principal (shareholders) and also the agent (company management). This general meeting that was held once a year is very meaningful in promoting good governance. Thus, it requires management consider to disclose the AGM minutes on the corporate website. The awareness of the certain companies in displaying timeliness, questions & answers, page number, attendance list, and chairman signatory should be used as a good disclosure example. Based on the researcher's observation, there is lacking studies that lead to the analysis of AGM minutes that should be explored in producing good governance.